Dapagliflozin Does Not Affect Short-Term Blood Pressure Variability in Patients With Type 2 Diabetes Mellitus. (22nd March 2021) - Papadopoulou, Eirini; Theodorakopoulou, Marieta P; Loutradis, Charalampos; Tzanis, Georgios; Tzatzagou, Glykeria; Kotsa, Kalliopi; Zografou, Ioanna; Tsapas, Apostolos; Karagiannis, Asterios; Sarafidis, Pantelis
Abstract: Background: Increased blood pressure variability (BPV) is associated with increased cardiovascular and all-cause mortality in patients with type-2 diabetes mellitus (T2DM). Sodium-glucose co-transporter 2 (SGLT-2) inhibitors decrease the incidence of cardiovascular events, renal events, and death in this population. This study aimed to evaluate the effect of dapagliflozin on short-term BPV in patients with T2DM. Methods: This is a secondary analysis of a double-blind, randomized, placebo-controlled trial in 85 patients with T2DM. Subjects were randomized to dapagliflozin 10 mg/day or placebo for 12 weeks. All participants underwent 24-hour ambulatory blood pressure (BP) monitoring with Mobil-O-Graph-NG device at baseline and study-end. SD, weighted SD (wSD), coefficient of variation, average real variability (ARV), and variation independent of mean were calculated for the 24-hour, daytime and nighttime periods. Results: Dapagliflozin reduced 24-hour brachial BP compared with placebo. From baseline to study-end 24-hour brachial BPV indexes did not change with dapagliflozin (SBP-ARV: 11.51 ± 3.45 vs. 11.05 ± 3.35; P = 0.326, SBP-wSD: 13.59 ± 3.60 vs. 13.48 ± 3.33; P = 0.811) or placebo (SBP-ARV: 11.47 ± 3.63 vs. 11.05 ± 3.00; P = 0.388, SBP-wSD: 13.85 ± 4.38 vs. 13.97 ± 3.87; P = 0.308). Similarly, no significant changes in BPV indexes for daytime and nighttime were observed in any group. At study-end, no between-group differences were observed for any BPV index. Deltas (Δ) of all indexes during follow-up were minimal and not different between groups (SBP-wSD: dapagliflozin: −0.11 ± 3.05 vs. placebo: 0.12 ± 4.20; P = 0.227). Conclusions: This study is the first to evaluate the effects of an SGLT-2 inhibitor on short-term BPV in T2DM, showing no effect of dapagliflozin on all BPV indexes studied. Clinical trials registration: Trial Number NCT02887677. Graphical Abstract: